Design and performance of final optics assembly in SG-II Upgrade laser facility. (19th April 2018) - Jiao, Zhaoyang; Shao, Ping; Zhao, Dongfeng; Wu, Rong; Ji, Lailin; Wang, Li; Xia, Lan; Liu, Dong; Zhou, Yang; Ju, Lingjie; Cai, Zhijian; Ye, Qiang; et al.
Abstract : In high power laser facility for inertial confinement fusion research, final optics assembly (FOA) plays a critical role in the frequency conversion, beam focusing, color separation, beam sampling and debris shielding. The design and performance of FOA in SG-II Upgrade laser facility are mainly introduced here. Due to the limited space and short focal length, a coaxial aspheric wedged focus lens is designed and applied in the FOA configuration. Then the ghost image analysis, the focus characteristic analysis, the B integral control design and the optomechanical design are carried out in the FOA design phase. In order to ensure the FOA performance, two key technologies are developed including measurement and adjustment technique of the wedged focus lens and the stray light management technique based on ground glass. Experimental results show that the design specifications including laser fluence, frequency conversion efficiency and perforation efficiency of the focus spot have been achieved, which meet the requirements of physical experiments well.